Pendampingan Guru Sekolah Menengah Pertama dalam Menyusun Perangkat Pembelajaran Sesuai Kurikulum Merdeka Berbasis ICT - Rohantizani, Rohantizani; Nuraina, Nuraina; Nufus, Hayatun; Anil Husna, Jaza; Manurung, Fatimah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This community service activity is motivated by the lack of competency of junior high school teachers in creating ICT-based learning tools that suit the independent curriculum and the lack of teacher creativity in developing learning tools, especially ICT-based teaching modules. This service was carried out at SMPN 4 Dewantara and SMPN 8 Lhokseumawe with the aim of increasing teacher competence in designing and implementing learning tools based on the Independent Curriculum and information technology. This program uses the lesson study method, where teachers are divided into small groups to develop teaching modules, Student Worksheets, and innovative learning media. Intensive training and guidance is provided to ensure that the devices developed are in accordance with students' needs and support ICT-based learning. The evaluation results show that this program succeeded in increasing teachers' understanding of the Independent Curriculum with an average of 3.69 and a percentage of 92.2%. Guidance in designing ICT-based teaching modules was considered very helpful, with an average of 3.84 and a percentage of 96.1%. Teachers feel more confident in using ICT, with an average of 3.72 and a percentage of 93%. The developed Student Worksheets is considered more interactive and interesting, although with an average of 3.4 and a percentage of 86%. The learning media and assessments designed are also considered effective, with a high percentage in the evaluation of relevance and comprehensiveness. Overall, satisfaction with the program was very high, with a mean of 3.91 and a percentage of 97.7%. This program shows a significant positive impact in improving the quality of learning and teacher abilities, as well as providing long-term benefits in implementing the ICT-based Independent Curriculum. The output of this community service is scientific publications in accredited journals and publication of activities in print or online media.